L’idea di progresso nel XVIII secolo: tra utopia e storia - Coratti, Antonio (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2023)
The idea of progress in the eighteenth century was born on assumptions that the philosophies of the history of the following century deeply betrayed, above all by deforming the link between utopia and reform that had inspired all the great philosophes in the eighteenth century. Starting from the analysis of the works of Mercier and Condorcet, the article highlights the relationship between history and utopia by setting it up as a central theme to rediscover the legitimacy of the Enlightenment era.